Wellbeing and clinical videoconferencing satisfaction among patients in psychotrauma treatment during the coronavirus pandemic: cross-sectional study. Issue 1 (1st January 2021) - ter Heide, F. Jackie June; de la Rie, Simone; de Haan, Annelies; Boeschoten, Manon; Nijdam, Mirjam J.; Smid, Geert; Wind, Tim; Mooren, Trudy
ABSTRACT: Background : The coronavirus pandemic appears to put psychiatric patients with pre-existing symptomatology at risk of symptom increase, but evidence is scarce. While the pandemic and stringent governmental measures have accelerated the use of clinical videoconferencing (VCT), patient satisfaction with VCT is unclear. Objective : Aim of the study was to assess the wellbeing of patients in psychotrauma treatment during the coronavirus pandemic and to evaluate their use of and satisfaction with VCT. Method : This study used data from a routine outcome monitoring assessment completed by patients in treatment at a specialized psychotrauma institute and administered before the easing of governmental measures in June 2020. Wellbeing (Brief Symptom Inventory, Cantril Ladder, perceived stress level, and symptom change), VCT use and VCT satisfaction, and their association with demographic variables (gender, age, education level, and refugee status) were analysed. Results : Of the 318 respondents (response rate 64.5%), 139 (43.7%) reported a symptom increase, which was associated with a higher coronavirus-related stress level and general psychopathology as well as lower life satisfaction. There were significant effects of age and education level on wellbeing. VCT was reported to have been used by 228 (71.7%) patients. VCT satisfaction ratings were higher among women and those with lower levels of stress ( r = −.20, p < .01) and general psychopathology ( r = .21, p < .01). No difference in treatment satisfaction was found between patients who used VCT versus those who did not (mean difference = −.09 95% CI: −.79 to .62, p = .81). Conclusions : The coronavirus pandemic has aggravated mental health complaints according to a substantial percentage of patients in psychotrauma treatment. Although VCT was found to be acceptable, face-to-face treatment may remain necessary for specific target groups with limited access to VCT (such as refugees) and patients with high levels of general psychopathology. HIGHLIGHTS: The coronavirus pandemic may aggravate existing mental health problems and has quickened the implementation of clinical videoconferencing (VCT). In this study, the majority of patients in treatment for psychotrauma felt worse during the corona crisis, but VCT offered some relief.